Analysis Of The Influence Of Macroeconomic And Banking Health Indicators On Islamic Banks Financing In Indonesia - Azhar Azhar (Proceeding International Seminar of Islamic Studies, 2019)
The study aims to reveal the macroeconomic influence (inflation and The exchange rate) as well as bank health indicators (ratio of financing to third party funds, ratio of operating expenses to income divided by operating income, ratio of non-performing financing). in analyzing the relationship between variables econometrics are used. Total for 51 months from June 2015 to June 2019. The results of the study are as follows: Macroeconomic variables and indicators of sharia banking health simultaneously influence Islamic bank financing in Indonesia during the study period. Partial inflation has a negative and significant effect on Islamic Bank financing in Indonesia, and the Rupiah exchange rate against the dollar has a positive and significant effect on Islamic Bank financing in Indonesia. Partially, the ratio of financing to third party funds (FDR) and the ratio of operating income to revenue divided by operating income (BoP0) have a significant negative impact on Islamic banking financing in Indonesia, while the non-performing financing ratio (NPF) has a positive and significant effect on Islamic Banking financing in Indonesia . Needed attention to inflation and exchange rates and bank health indicators do not interfere and counter productive to the performance of Islamic banking financing in Indonesia.